Perforated peptic ulcer disease: mid-term outcome among Iranian population - Freshteh KAMANI,; Mehrdad MOGHIMI,; Seyed Ali MARASHI,; Habibollah PEYROVI,; Mehrdad SHEIKHVATAN, (Turkish Journal of Gastroenterology, 2019)
-